Role of Endoscopic Ultrasound to Assess and Manage Portal Hypertension - Singh, Sidhant; Mukewar, Saurabh (Digestive Disease Interventions, 2020)
Portal hypertension leads to the development of varices along the gastrointestinal tract. Endoscopy plays an important role in the diagnosis and management of varices. Endosonography (EUS) enables visualization and permits access to varices and veins outside the gastrointestinal tract. EUS has emerged as an important tool, with the ability to identify vascular changes, treat gastric and ectopic varices, perform portal pressure measurements, portal venography, and intrahepatic shunt placement. This review discusses the role of endoscopy and the emerging role of EUS in evaluation and management of portal hypertension.
Keywords: endoscopy; portal hypertension; endoscopic ultrasound